Is the international community helping to recreate the pre-conditions for war in Sierra Leone? - Joseph Hanlon (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
`In a very real sense, the conditions that spawned the war and inflicted gruesome casualties on Sierra Leone's citizens have not disappeared', warned the International Crisis Group. In this paper we argue that many of those conditions are being recreated. The same old men who were responsible for the war are still in power, both in government and in a reinstated chieftaincy system, and corruption is still endemic, while young people remain jobless and largely uneducated. Further, we argue that the policies of the international community are, perhaps inadvertently, promoting a return to pre-war conditions.
Keywords: F35; O55; N47; O17; 330; Sierra Leone; conflict; government; aid; corruption